(untitled) (Itinera, 2018)
The following essay is mainly concerned with materialism notion, considered as one of the very fundamental architraves of Giacomo Leopardi’s whole thought. This standpoint derives to him from Locke’s work, but our author became much more radical. The goal is to show how the pervasiveness of an integral materialistic point of view is able – in Leopardi’s layout – to effect even the linguistic scope, especially the poetic one. Our aim is to outline the potential ethical content, that the Italian thinker conveys in his pieces of advice to poets and writers.